Quantitative Mechanical Properties of the Relaxed Biceps and Triceps Brachii Muscles in Patients with Subacute Stroke: A Reliability Study of the Myoton-3 Myometer - Li-ling Chuang; Ching-yi Wu; Keh-chung Lin; Shih-yu Lur (Stroke Research and Treatment)
Objective. Test-retest reliability of the myotonometer was investigated in patients with subacute stroke. Methods. Twelve patients with substroke (3 to 9 months poststroke) were examined in standardized testing position twice, 60 minutes apart, with the Myoton-3 myometer to measure tone, elasticity, and stiffness of relaxed bilateral biceps and triceps brachii muscles. Intrarater reliability of muscle properties was determined using intraclass correlation coefficient (ICC), the standard error of measurement (SEM), and the minimal detectable change (MDC). Results. Intrarater reliability of muscle properties of bilateral biceps and triceps brachii muscles were good (ICCs=0.79–0.96) except for unaffected biceps tone (ICC=0.72). The SEM and MDC of bilateral biceps and triceps brachii muscles indicated small measurement error (SEM% <10%, MDC% <25%). Conclusion. The Myoton-3 myometer is a reliable tool for quantifying muscle tone, elasticity, and stiffness of the biceps and triceps brachii in patients with subacute stroke.